Rapid and colorimetric evaluation of G-series nerve agents and simulants using the squaraine-ethanolamine adducts. (January 2022) - Zhao, Jiayin; Qin, Molin; You, Jiawen; Liu, Ke; Ding, Liping; Liu, Taihong; Kong, Jinglin; Fang, Yu
Abstract: High toxicity and reactivity of chemical warfare agents (CWAs) have attracted increasing demand of reliable detection methods for countering terrorism. Herein, we report a chemical approach based on the squaraine-ethanolamine (SQ-ETA) adducts for rapid, sensitive, and selective detection of the G-series nerve agents and simulants in aqueous media. Present strategy features the merits of obvious turn-on response and colorimetric mode upon the presence of certain analytes. Possible sensing mechanism was the nucleophilic addition of ethanolamine toward the central SQ core to generate a SQ-ETA adduct firstly, supported by the additional NMR and MS characterizations. And special binding affinity of the G-series nerve agents and simulants to the hydroxyl groups in the SQ-ETA adducts thus recover the original SQs (SQOH and SQPY), endowing distinguishable colorless-to-blue change. The detection limits for diethyl chlorophosphate and diethyl cyanophosphonate were determined from the SQOH-ETA system to be 3.5 and 36.0 μM, respectively. In addition, the obtained adducts were further utilized to detect real G-series nerve agents including sarin (GB) and soman (GD), confirming the strategy suitable for on-site detection. In conjunction with smartphone-based analytical methodology, proper correlation between the RGB changes and substance concentrations was founded. Present successful trials inspire the semi-quantitative evaluation of G-series nerve agents with high accuracy and relative simplicity, implying great potential in detecting CWAs. Graphical abstract: Image 1 Highlights: The squaraine-ethanolamine adducts are developed for detecting G-series nerve agents in aqueous media. Present strategy exhibits colorimetric, timely, and turn-on response to the simulants. Inspiring on-site detection of sarin and soman with simple operation are conducted. Semi-quantitative evaluation with high accuracy is achieved.